Effect of maternal preconceptional and pregnancy micronutrient interventions on children's DNA methylation: Findings from the EMPHASIS study. Issue 4 (5th September 2020) - Saffari, Ayden; Shrestha, Smeeta; Issarapu, Prachand; Sajjadi, Sara; Betts, Modupeh; Sahariah, Sirazul Ameen; Tomar, Ashutosh Singh; James, Philip; Dedaniya, Akshay; Yadav, Dilip K; Kumaran, Kalyanaraman; Prentice, Andrew M; et al.
ABSTRACT: Background: Maternal nutrition in pregnancy has been linked to offspring health in early and later life, with changes to DNA methylation (DNAm) proposed as a mediating mechanism. Objective: We investigated intervention-associated DNAm changes in children whose mothers participated in 2 randomized controlled trials of micronutrient supplementation before and during pregnancy, as part of the EMPHASIS (Epigenetic Mechanisms linking Preconceptional nutrition and Health Assessed in India and sub-Saharan Africa) study (ISRCTN14266771). Design: We conducted epigenome-wide association studies with blood samples from Indian ( n = 698) and Gambian ( n = 293) children using the Illumina EPIC array and a targeted study of selected loci not on the array. The Indian micronutrient intervention was food based, whereas the Gambian intervention was a micronutrient tablet. Results: We identified 6 differentially methylated CpGs in Gambians [2.5–5.0% reduction in intervention group, all false discovery rate (FDR) <5%], the majority mapping to ESM1, which also represented a strong signal in regional analysis. One CpG passed FDR <5% in the Indian cohort, but overall effect sizes were small (<1%) and did not have the characteristics of a robust signature. We also found strong evidence for enrichment of metastable epialleles among subthreshold signals in the Gambian analysis. This supports the notion that multiple methylation loci are influenced by micronutrient supplementation in the early embryo. Conclusions: Maternal preconceptional and pregnancy micronutrient supplementation may alter DNAm in children measured at 7–9 y. Multiple factors, including differences between the nature of the intervention, participants, and settings, are likely to have contributed to the lack of replication in the Indian cohort. Potential links to phenotypic outcomes will be explored in the next stage of the EMPHASIS study.